The Effect Of Financial Performance On Capital Structure And Its Implications For Firm Value In Non-Primary Consumption Companies - Vira Anggraini; Enggar Diah Puspa Arum; Rahayu Rahayu (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to analyze the impact of liquidity, solvency, and profitability on firm value in non-primary consumer firms listed on the Indonesia Stock Exchange (IDX), with capital structure as a mediating variable. Understanding these financial factors is crucial, as firm value reflects investor confidence and overall business sustainability. The study utilizes secondary data from the past three years' financial statements. Path analysis and the Sobel test are employed to examine both direct and mediating effects. The findings indicate that solvency positively influences capital structure but does not affect firm value, while liquidity has no significant impact on either. Profitability positively affects firm value but negatively influences capital structure. Additionally, capital structure does not mediate the relationship between liquidity and firm value or between profitability and firm value. However, it has a significant positive effect on firm value. These results suggest that while capital structure plays a role, investors also consider other factors, such as investment strategies and financial policies, when assessing firm value. The findings provide insights for businesses and investors regarding financial decision-making and firm valuation in the non-primary consumer sector.